Comparative Effects of Ingested PVC Micro Particles With and Without Adsorbed Benzo(a)pyrene vs. Spiked Sediments on the Cellular and Sub Cellular Processes of the Benthic Organism Hediste diversicolor - Gomiero, Alessio; Strafella, Pierluigi; Pellini, Giulio; Salvalaggio, Vera; Fabi, Gianna (Frontiers in Marine Science, 2018)
The plastic microliter represents an emerging contaminant as well as multiple stress agent in the aquatic environments. Microplastics are found even in the remote areas of the world. Together with their occurrence in all environmental compartments, there is a growing concern about their potential of adsorbing pollutants co-occurring in the environment. Currently, little is known about this source of exposure for aquatic organisms in the benthic environment. Exposure conditions were set up mimicking the contribution of microplastics in different exposure routes. The potential biological effects were investigated in the model organism: the annelid Hediste diversicolor. Cellular effects including alterations of immunological responses, lysosomal compartment, mitochondrial activity, oxyradical production and onset of genotoxicity were assessed in coelomocytes while temporary and permanent effects of oxidative stress were also performed at tissue level. In this study polyvinylchloride (PVC) microplastics were shown to adsorb benzo(a)pyrene with a time and dose-dependent relationship. Results also indicated a marked capability of contaminated microplastics to transfer the model organic chemical to exposed model organism under physiological gut conditions and concentrated in tissues. The elevated bioavailability of the model pollutant after the ingestion induced a clear pattern of biological responses. Toxicity mainly targeted impairment of cellular functioning and genotoxicity in ragworm’s coelomocytes, while permanent effects of oxidative stress were observed at tissue level. Coelomocytes responded faster and with a higher degree of sensitivity to the adverse stimuli when compared with responses observed in whole tissue samples. The results showed that microplastic particles in sediments may play a significant role as vectors for organic pollutants. The highest adverse responses were observed in those ragworms exposed to sediments spiked with PVC particles pre-incubated with B[a]P when compared against sediments spiked with B[a]P and microplastics separately.